Efficacy of chronic statin therapy on major cardiac events after coronary artery bypass grafting: low-dose versus high-dose - Ayşegül Kunt; Sedat Özcan; Aslihan Küçüker; Dolunay Odabaşi; Alper Sami Kunt (Medicinski glasnik, 2015)
Aim: To investigate whether chronic statin treatment after coronary artery bypass grafting (CABG) protects patients from major cardiac events and provides percutaneous coronary intervention (PCI) free survival. Methods: A total of 232 patients with previous CABG and chronic statin therapy were selected retrospectively and were divided into two groups according to a dosage of atorvastatin per day, e. g., 20 mg or 40 mg. Groups were compared for the major cardiac events and freedom from PCI by Kaplan Meier analysis as the primary end point. Patency of grafts including left internal thoracic artery (LITA) and saphenous vein (SVG) and progression of non-grafted native vessel disease were also evaluated as secondary end points. Results: Cardiac mortality, periprocedural myocardial infarction (MI), target vessel revascularization and percutaneous coronary intervention free survival were as follows: 2.9% versus 2.1% (p=1.000); 16.1% versus 21.1% (p=0.331); 56.93% versus 52.63% (p>0.005); 58.4% versus 63.2% (log-rank test; p= 0.347) in atorvastatin 20 mg and atorvastatin 40 mg groups, respectively. However, these results were not statistically significant between two groups (p>0.005). Patency of openness of grafts including LITA and SVG and progression of non-grafted native vessel disease were similar between groups (p=0.112, p=0.779, p=0.379 and p=0.663, respectively). Conclusion: Low-dose long-term statin treatment had similar outcomes on major cardiac events and identical rate of freedom from percutaneous coronary intervention after coronary artery bypass grafting compared with high-dose long-term statin treatment. It is better to start from low dose statin treatment after surgical interventions.
Keywords: chronic statin treatment; major cardiac events; coronary bypass grafting